Application of serious games in chemical engineering courses - Díaz, Ismael; González, Emilio J.; González-Miquel, María; Rodríguez, Manuel (Education for chemical engineers, 2024)
The advantages of using elements of games in educational contexts have been reported in literature since the times of Plato in ancient Greece. Modern studies credited games with some advantages in education from different angles (behavioural, motivational or cognitive). In this paper, the application of games that have an explicit and carefully thought-out educational purpose (serious games) in different chemical engineering subjects at the bachelor and master level is discussed. Firstly, some topic definitions are provided along with a historical perspective of the use of games in education and the theoretical foundations supporting it. In section 2, four different applications of games are presented in three different subjects. In particular, the use of board games for the subjects Process Control and Particle Technology is illustrated, and how the combination of simple games (e.g. crosswords) and escape room activities can help to develop both low level and high level skills (following the Bloom’s taxonomy classification) in Optimisation of Chemical Processes is also presented. Their analysis and discussion of the impacts achieved with the different game-based activities are later presented in section 3 along with the main conclussions drawn. •Serious games can help to promote active learning, engagement, and motivation of chemical engineering students.•Different game-based activities were implemented to foster both low level and high level skills.•A comprehensive design to adapt the type and level of the games to the classroom is key to promote positive impacts.